School trajectories of adolescents in conflict with the law: Systematic and integrative review - Lima, Francisca Vieira; Haracemiv, Sonia Maria Chaves (Education Policy Analysis Archives, 2021)
The present study presents a systematic and integrative review and aims to investigate the contributions of research related to the school trajectories of adolescent students/ graduates in/of socio-educational measures in an open environment. The search for scientific productions was carried out based on specific criteria with the platforms: Digital Library of Theses and Dissertations (BDTD / IBCT), Scientific Electronic Library Online (SciELO) and Coordination for the Improvement of Higher Education Personnel (CAPES). The methodology involved the selection of 105 scientific works that, after reading the abstracts, resulted in six productions that were submitted to a full reading for further integrative analysis. It was found that the school trajectories of these subjects are marked by processes of age-grade lag, repetition and school supply. Despite the negative school marks registered in the adolescents' lives, the school is a form of “protection”, signaling the need for investments in pedagogical practices that recognize the peculiarities of these individuals.